Electronic reporting of all reference laboratory results: An important step toward a truly all-encompassing, integrated health record. (September 2016) - Kratz, Alexander
Results from reference laboratories are often not easily available in electronic health records. This article describes a multi-pronged, long-term approach that includes bringing send-out tests in-house, upgrading the laboratory information system, interfacing more send-out tests and more reference laboratories, utilizing the "miscellaneous assay" option offered by some reference laboratories, and scanning all remaining paper reports from reference laboratories for display in the electronic health record. This allowed all laboratory results obtained in association with a patient visit, whether performed in-house or at a reference laboratory, to be available in the integrated electronic health record. This was achieved without manual data entry of reference laboratory results, thereby avoiding the risk of transcription errors. A fully integrated electronic health record that contains all laboratory results can be achieved by maximizing the number of interfaced reference laboratory assays and making all non-interfaced results available as scanned documents.